Psychological Capital and Job Satisfaction Among Chinese Residents: A Moderated Mediation of Organizational Identification and Income Level - Zhang, Fang; Liu, Ying; Wei, Tongqi (Frontiers in Psychology, 2021)
The present study examined the mediating effect of organizational identification on the relationship between psychological capital and job satisfaction, and whether the mediation was moderated by income level. A total of 310 Chinese residents were surveyed using the Psychological Capital Scale, Organizational Identification Scale, Job Satisfaction Scale, and a demographic questionnaire. The findings showed a significant positive correlation between psychological capital and job satisfaction of residents, and this relationship was partially mediated by organizational identification. Moreover, income level played a moderating role in the relationship between organizational identification and job satisfaction. For residents with more income, their organizational identification influenced their job satisfaction more strongly than those with less income. The current study contributes to a better understanding of the relationship between psychological capital and job satisfaction. Implications for resident management and policymaking are discussed.